STOCHASTIC MODELING AND SENSITIVITY ANALYSIS OF AN INTEGRATED HARDWARE-SOFTWARE SYSTEM SUBJECT TO DIFFERENT WEATHER CONDITIONS - Saini, Monika; Kumar, Ashish (Malaysian Journal of Science, 2021)
The current study covenants with stochastic investigation of an integrated hardware-software system considering hardware failure, software up-gradation upon failure, precautionary maintenance (PM) after a pre-determined process time, maximum repair time of hardware and different weather conditions. All time dependent indiscriminate variables are arbitrarily dispersed. Some important reliability measures like MTSF, availability and revenue of the system are obtained by using well established techniques semi-Markov process. Regenerative point technique has also been taken into consideration during model development. Sensitivity analysis of these measures is also performed. Finally, empirical analysis is done to demonstrate the results for a specific case. To climax the significance of the study, graphs of MTSF, availability, profit and sensitivity are also depicted.